2019
DOI: 10.1007/s42452-019-0207-z
|View full text |Cite
|
Sign up to set email alerts
|

Phase evolutions and growth kinetics in the Co–Sn system

Abstract: Co/Sn diffusion couples are annealed at 175-220 °C. The reaction phase CoSn 3 is found to have a narrow homogeneity range of 2 at% with composition 74-76 at% Sn. The growth of this phase is found to be reaction-controlled initially followed by diffusion-controlled later. The marker experiment indicates that Sn is the faster diffusing element in this phase. The CoSn 2 phase is found to grow in the Co/CoSn 3 incremental couples at 200-220 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…It is well known that for constant temperature, phase growth (ω) maintains the parabolic relationship with time (t) as ω 2 = 2Kt, where K is the coefficient of phase growth [8,9]. The determination of K is carried out by the use of linear regression analysis of ω 2 and t data.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that for constant temperature, phase growth (ω) maintains the parabolic relationship with time (t) as ω 2 = 2Kt, where K is the coefficient of phase growth [8,9]. The determination of K is carried out by the use of linear regression analysis of ω 2 and t data.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies [38][39][40] have identified that at low temperatures below 300 °C, the first forming phase in Sn and Co reactions is CoSn3. However, referring to the Sn-Co phase equilibrium diagram [41,42], it is evident that the melting point of CoSn3, at 345 °C, is insufficiently high for our purposes. At 280 °C, the homologous temperature (T/Tm) for CoSn3 is approximately 0.9, indicating its incapability to withstand the high-temperature demands of power device junctions.…”
Section: Correlation Between Microstructure and Mechanical Reliabilitymentioning
confidence: 92%